Relationships between occupational stress, organizational commitment and teacher performance at university level in Pakistan - Azeem, Nazia; Omar, Muhd Khaizer (Faculty of Educational Studies, Universiti Putra Malaysia, 2018)
The basic intend of this research is to find out the relationships between occupational stress, organizational commitment and the teacher performance at university level in Punjab, Pakistan. All faculties of the public university teacher of Education Departments of Punjab were included in population of this study. A convenient sample of 100 teachers and 500 students (5 students of each teacher) were selected from the public universities of Punjab. The sample included of 54 % of female teachers and 46 % of male teachers. Teachers’ age ranging from 25 to 55 years old. Teacher's qualification ranging from Master of Arts (MA)/Master of Science (MS) to Ph.D. Teachers experienced ranging from 1 to 30 years. Other specifications of sample were job position and job status. The questionnaires were used as a research instrument. Result of the research shows that there is positive relationship between occupational stress and organizational commitment and have found no relationship between occupational stress and teacher performance or between organizational commitment and teacher performance at university level in Punjab. This paper extends knowledge and offers recommendations for practice and research.